The Efficacy of Tai Chi and Stretching Exercises Based on a Smartphone Application for Patients With Parkinson's Disease: A Protocol for a Randomized Controlled Trial - Ma, Renyan; Hou, Yuning; Zhang, Yiyin; He, Muyang; Gao, Song; Kaudimba, Keneilwe Kenny; Lin, Kaiqing; Jin, Lingjing; Liu, Tiemin; Wang, Ru (Frontiers in Neurology, 2021)
Introduction: Parkinson's disease (PD) is a common neurodegenerative disease that seriously impairs patients' quality of life, and increases the burden of patients and caregivers. Both drugs and exercise can alleviate its motor and non-motor symptoms, improving the quality of life for PD patients. Telehealth, an increasingly popular tool, makes rehabilitation accessible at home, overcoming the inconvenience of traffic and scheduling. Care-PD is a phone application designed for rehabilitation training, which provides Tai Chi and stretching exercises through tutorial videos as well as an online evaluation system. In this protocol, we will explore the efficacy of Tai Chi and stretching exercises as a PD rehabilitation therapy based on the smartphone application Care-PD. Methods and Analysis: A double-blind, parallel randomized controlled trial will be conducted in this study. The recruitment, intervention, and evaluation processes will be implemented through the Care-PD application. Persons with PD will fill out questionnaires on Activities of Daily Living (ADL), upload the latest case report, and sign the informed consent form in the application. Afterward, doctors and researchers will screen and enroll 180 participants who will be randomly (1:1:1) assigned to Tai Chi group, stretching exercises group, or control group. The subjects will participate in a 1-h exercise session three times per week for 12 weeks, ending with another 4 weeks of follow-up study. Each exercise session includes 10 min of warm-up, 45 min of exercise, and 5 min of cool-down. The primary outcomes are Motor Aspects of Experiences of Daily Living and the 39-item Parkinson's disease Questionnaire. The secondary outcomes include the 9-item Wearing-Off Questionnaire, the Freezing of Gait Questionnaire, the Caregiver Strain Index, Non-motor Experiences of Daily Living, ADL, and Morse Fall Scale. All assessments will be performed at baseline, week 12 and 16. Discussion: Care-PD integrates subject recruitment, intervention, and evaluation, providing a new perspective on clinical rehabilitation for persons with PD. This study will evaluate the efficacy of Tai Chi and stretching exercises on patients' quality of life and disease progression based on a smartphone application. We aim to provide a new rehabilitation training platform for persons with PD. Ethics and Dissemination: This study was approved by the Scientific Research Ethics Committee (102772020RT132) of Shanghai University of Sport. Data collection begins after the approval of the ethics committee. The participants must sign an informed consent form before enrollment. The results will be published in relevant journals, seminars, and be disseminated among rehabilitation practitioners and patients with PD. Clinical Trial Registration: Chinese Clinical Trial Registry, identifier [ChiCTR2100042096]. Registered on January 13, 2021.